(3GdaUhd GdNeShfs - (3GHf eYWj , jMji Hf YHO GdeYWj Hf YHO GdfhQ GdRhGhj, Rjf GdOjf CHh GdMSjf,J (B628 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEf ZQV GdeHJOF GdQGZH aj Yde GdEYQGH MUQJg aj NeSjf aUdkG s
(3BNQgG (B:s
(3aCUHMJ HYO NW HgLJgG cCf baQkG QShegG bdeG Pdc GdEOZGe GdTGP haj Hfj GdYfHQ heKdg bhdg hdcf hddg GdMeO ChdkG hBNQkG s
(3GfXQ GdLRA GdChd (B123 (3fMh HYfhGf GdaUhd GdfMhjIs
(3HgG fXGe GdJYbjHIs
(3CKQ WeSs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdfMhs